Estimated number of injection-involved drug overdose deaths, United States, 2000 – 2018. (1st May 2022) - Hall, Eric W.; Rosenberg, Eli S.; Jones, Christopher M.; Asher, Alice; Valverde, Eduardo; Bradley, Heather
Abstract: Background: In the United States, drug overdose mortality has increased. Death records categorize overdose deaths by type of drug involved, but do not include information about the route of drug administration. Methods: We utilized data from drug treatment admissions (Treatment Episodes Dataset, TEDS-A) and National Vital Statistics Systems to estimate the percentage of reported drug overdose deaths that were injection-involved from 2000 to 2018 in the U.S. Data on reported route of administration at admission were used to calculate the percent injecting each drug type, by demographic group (race/ethnicity, sex, age group) and year. Using the resulting probabilities, we estimated the number of overdose deaths that were injection-involved. Estimates were compared across drug types, demographic characteristics, and year. Findings: The number of overdose deaths among adults increased more than 3-fold from 2000 (n = 17, 196) to 2018 (n = 67, 021). During that timeframe, the number of estimated injection-involved overdose deaths increased more than 8-fold from 2000 (n = 3467, 95% CI: 3449–3485) to 2018 (n = 28, 257, 95% CI: 28, 192–28, 322). From 2000–2007, the percent of overdose deaths that were injection-involved remained stable around 20%. From 2007–2018, the percent of overdose deaths that were injection-involved increased from 18.4% (95% CI: 18.3–18.6%) to 42.2% (95% CI: 42.1–42.3%). In 2018, most estimated injection-involved overdose deaths were due to injecting heroin/synthetic opioids (n = 24, 860, 95% CI: 24, 800–24, 919), which accounted for 88.0% of all injection-involved deaths. Conclusions: Much of the recent increase in overdose mortality is likely attributable to rising injection-involved overdose deaths. Highlights: Injection-involved overdose deaths have increased 8-fold from 2000 to 2018. Much of the increase in overdose mortality is attributable to injection-involved overdose deaths. The magnitude of the increase in injection involvement in overdose deaths differs across demographic groups. In 2018, a higher proportion of overdose deaths among adults 18–39 years of age involved injection (54.4%) compared to adults 40 + years of age (32.7%).